Aprepitant for the prevention of chemotherapy‐induced nausea and vomiting in paediatric subjects: An analysis by age group - Kang, Hyoung Jin; Loftus, Susan; DiCristina, Cara; Green, Stuart; Pong, Annpey; Zwaan, Christian Michel (Pediatric blood & cancer, 2018)
Background This was a subgroup analysis of age group, dexamethasone use, and very highly emetogenic chemotherapy (VHEC) use from a randomised, multicentre, double‐blind, Phase 3 study of oral aprepitant in paediatric subjects. Methods Subjects aged 6 months to 17 years scheduled to receive chemotherapeutic agents associated with at least moderate risk for emesis were randomly assigned to receive either aprepitant plus ondansetron (aprepitant regimen) or placebo plus ondansetron (control regimen); both could be administered with or without dexamethasone. This secondary analysis evaluated subjects stratified by pre‐specified age groups, dexamethasone use, and VHEC use. The primary endpoint of this analysis was the proportion of subjects who experienced complete response (CR) during the delayed phase. Results CR rates in the delayed phase were numerically higher with the aprepitant than the control regimen across all age categories, and reached significance for subjects aged 12–17 years (51% vs. 10%; P < 0.0001). In subjects receiving dexamethasone, CR was twice as high for the aprepitant versus control regimen in the 6 months to <2 year group (50% vs. 25%) and significantly higher in the 12–17 year group (40% vs. 7%, P < 0.05). CR was also significantly higher with aprepitant in the 6 months to <2 year and 12–17 year age groups who received VHEC. Similar proportions of subjects experiencing at least one adverse event were seen in both regimens across age categories. Conclusion A 3 day aprepitant regimen seemed effective and safe for prevention of chemotherapy‐induced nausea and vomiting in paediatric subjects across subgroups (ClinicalTrials.gov NCT01362530).